1979
DOI: 10.1128/iai.23.3.670-674.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabinoids on host resistance to Listeria monocytogenes and herpes simplex virus

Abstract: Previous investigations from our laboratories have demonstrated that cannabinoids possess immunosuppressive properties. The present studies were designed to determine whether these agents decrease host resistance to infections with Listeria monocytogenes and herpes simplex virus type 2. Host resistance was measured by changes in the 50% lethal dose of the pathogen in cannabinoidtreated and control mice. The effect of cannabinoids on resistance to L. monocytogens was dose dependent. Delta-9-tetrahydrocannabinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…These ECS components include several endogenously synthesized and degraded cannabinoid-like fatty acid amides and n-arachidonyl amino acids together with their receptors and primary inactivating enzyme FAAH. Earlier studies of exogenous cannabinoids such as ⌬ 9 -tetrahydrocannabinol and se- lected endogenous cannabinoids have demonstrated immune suppression with effects ranging from loss of resistance to infection [23,24] to inhibition of lymphocyte proliferation [20]. More recent studies of endocannabinoids in mammals have shown a complex range of immunomodulatory effects, primarily suppressive effects on leukocytes and immune functions [5], including modulation of Th cell development, chemotaxis, and cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…These ECS components include several endogenously synthesized and degraded cannabinoid-like fatty acid amides and n-arachidonyl amino acids together with their receptors and primary inactivating enzyme FAAH. Earlier studies of exogenous cannabinoids such as ⌬ 9 -tetrahydrocannabinol and se- lected endogenous cannabinoids have demonstrated immune suppression with effects ranging from loss of resistance to infection [23,24] to inhibition of lymphocyte proliferation [20]. More recent studies of endocannabinoids in mammals have shown a complex range of immunomodulatory effects, primarily suppressive effects on leukocytes and immune functions [5], including modulation of Th cell development, chemotaxis, and cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular and cellular mechanisms for these effects are not completely defined, it is believed that both receptor and non-receptor mechanisms are involved. Two major cannabinoid receptors have been extensively studied (Mechoulam et al, 1969;Morahan et al, 1979;Mishkin & Cabral, 1985;Ashfaq et al, 1987;Matsuda et al, 1990;Specter et al, 1991;Munro et al, 1993;Paradise & Friedman, 1993;Klein et al, 1993Klein et al, , 2000Newton et al, 1994). The receptors CB1 and CB2 have been purified and shown to be G-protein-coupled 7-transmembrane molecules.…”
Section: Cannabinoid-induced Immunomodulation and Susceptibility To Imentioning
confidence: 99%
“…Various studies during the last decades have shown that cannabinoids have marked effects on resistance to infectious diseases, both intracellular opportunistic bacteria and a wide variety of viruses (Morahan et al, 1979;Mishkin & Cabral, 1985;Ashfaq et al, 1987;Specter et al, 1991;Paradise & Friedman, 1993;Klein et al, 1993Klein et al, , 2000Newton et al, 1994Newton et al, , 1998. For example, laboratory studies with rodents have shown that specific cannabinoids alter susceptibility to intracellular bacteria such as Listeria, Legionella, and even Treponema pallidum, the etiologic cause of syphilis, as well as to the herpes simplex virus, and, although still controversial, they may contribute to the more rapid progression of HIV-infected individuals to clinical AIDS and to increased susceptibility to opportunistic microbial infection (Table 3).…”
Section: Immune Modulation By Drugs Of Abusementioning
confidence: 99%
“…Some of these immunological defects are likely due to disruptions in T-cell interactions with antigen-presenting cells (Berdyshev, 2000). In addition to these in vitro effects, it has been shown that administration of high-dose THC in mice resulted in decreased resistance to Listeria monocytogenes or Herpes simplex virus (Morahan et al, 1979). Although the list of possible immunological perturbations by the endocannabinoid system is extensive, regulation of any specific immune response that results in autoimmunity or protective immunity are not well studied or understood.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%